Financial Planning and Management Training for the Pasuluhan Village Community, Serang City in the Era of the Covid-19 Pandemic - Stannia Cahaya Suci; Cep Jandi Anwar; Vadilla Mutia Zahara; Rah Adi Fahmi Ginanjar (LPPM UIKA Bogor, 2022)
The decline in people's income due to limited economic conditions at the start of the Covid-19 Pandemic increased awareness of the importance of knowledge of family financial management. Therefore the need for community empowerment activities through the presentation of material on how to manage good finances and other financial knowledge so that the community's economy will increase and reduce the risk of financial problems in the future. The method used was the presentation of material by competent sources during the Covid pandemic, but still paying attention to health protocols. The result of this activity is the increased awareness of the village community regarding the proper management and recording of finances and income. In the long term, this activity is expected to contribute to increasing the level of national financial literacy.